MULTIKULTURALISME DALAM PERSPEKTIF AL-QUR'AN - Chirri, Nabila El (UIN Sumatera Utara Medan, 2025)
This study aims to explore how the concept of multiculturalism is viewed in the Qur'an, how Islamic scholars (mufassir) interpret verses related to multiculturalism, and to what extent multiculturalism influences the essence of being a Muslim. This research is classified as a library study, conducted by collecting various data and information relevant to the topic. The data were examined and analyzed through a study of books, Qur'anic commentaries (tafsir), and scholarly articles related to the subject. The research produced three main findings. First, the Qur'an supports multicultural values, as reflected in several verses that address the diversity of tribes and nations (Q.S. Al-Hujurāt/49:13), the fact that humanity was not created as a single homogeneous community (Q.S. Al-Māidah/5:48), and the call for justice toward all people regardless of their faith or ethnicity (Q.S. Ali ‘Imrān/3:64). Additionally, the Qur'an affirms that there should be no compulsion in religion (Q.S. Al-Kāfirūn/109:6), and that the Prophet Muhammad (peace be upon him) was sent as a mercy to all of humanity, irrespective of religious background (Q.S. Al-Anbiyā’/21:107). Second, classical commentators such as Abū Ja‘far aṭ-Ṭabarī (d. 310 AH) and Ibn Kathīr (d. 774 AH) implicitly support the principle of multiculturalism through their interpretation of the word sawā’, understood as universal justice for all, whether Muslim or non-Muslim. Third, the influence of multiculturalism on Islamic identity lies in the understanding that a true Muslim must believe in Allah, have faith in the Last Day, and consistently perform good deeds for all of humanity without discrimination based on religion, nationality, race, language, or other differences.